Implementation of School-Based Mental Health Program on Teachers' Ability To Handle Students' Emotional And Behavioral Problems: One Group Pretest-Posttest Design - Wardiyah Daulay; Mahnum Lailan Nasution; Jenny Marlindawani Purba (Caring: Indonesian Journal of Nursing Science, 2025)
The increasing prevalence of emotional and behavioral problems among teenagers necessitates effective, early intervention. The World Health Organization recommends schools as key sites for mental health promotion. However, the sustainability of these programs is often a significant challenge. Empowering teachers to handle students' emotional and behavioral issues is a critical strategy to improve program sustainability. This study aimed to evaluate the impact of a school-based mental health program on teachers' abilities to manage students' emotional and behavioral problems. This study utilized a one-group pretest-posttest design. A total of 60 teachers from SMP Negeri 1 Tanjung Morawa participated as the sample. Teachers' abilities were measured using a questionnaire before (pretest) and after (posttest) the implementation of the school-based mental health program. Data were analyzed using a dependent t-test to compare the mean scores. A significant improvement in teachers' abilities was observed after the program. The mean ability score increased from 50.13 at pretest to 75.20 at posttest, representing a mean difference of 25.07 (a 50.01% increase). This increase was statistically significant (p < 0.001, with an alpha of 0.05). The school-based mental health program was effective and had a substantial influence on improving teachers' abilities to handle students' emotional and behavioral problems. These findings support teacher empowerment as a viable strategy for implementing and sustaining mental health programs in school setting. Keyword: Teacher, Student emotional problems, Behavioral problems